Transformasi Usia Perkawinan di Era Baru: Kajian Pasca UU No. 16 Tahun 2019 di Bengkulu Tengah Perspektif Maslahah Mursalah - Yusmita, Yusmita; Sitorus, Iwan Romadhan (QIYAS: JURNAL HUKUM ISLAM DAN PERADILAN, 2025)
Abstracts: The marriage age stipulated in Law No. 16 of 2019 as an amendment to Law No. 1 of 1974 concerning Marriage has provided significant benefits, where previously it was set at 16 years for women and 19 years for men, now it has changed to 19 years for men and 16 years for women. This change deserves recognition because the results of the struggle to revise Law No. 1 of 1974 have been approved by the Constitutional Court. The age provisions stipulated by the Constitutional Court, namely 19 years for men, are considered to reflect maturity in attitude, ability to act, and responsibility for the actions taken. Meanwhile, women who are 19 years old are considered adults and able to live a household life. When viewed from the perspective of the maslahah mursalah theory, this is related to the four main elements protected by religion, which are the initial objectives of legal syari'at. The four elements are the maintenance of offspring, soul, mind, and property in the context of the family. The issue regarding the minimum age limit for marriage is an area of ijtihadiyah which is always open to change in line with developments in conditions, society, time and place which require adjustment.Keywords: Transformation, Age of Marriage, Maslahah Mursalah Abstrak : Usia pernikahan yang diatur dalam Undang-Undang No 16 Tahun 2019 sebagai amandemen dari Undang-Undang No 1 Tahun 1974 tentang Perkawinan telah memberikan manfaat yang signifikan, di mana sebelumnya ditetapkan 16 tahun untuk perempuan dan 19 tahun untuk laki-laki, kini berubah menjadi 19 tahun untuk laki-laki dan 16 tahun untuk perempuan. Perubahan ini patut mendapat pengakuan karena hasil perjuangan untuk merevisi Undang-Undang No 1 Tahun 1974 telah disetujui oleh Mahkamah Konstitusi. Ketentuan usia yang ditetapkan oleh Mahkamah Konstitusi, yaitu 19 tahun untuk laki-laki, dianggap mencerminkan kematangan dalam sikap, kemampuan bertindak, serta tanggung jawab atas tindakan yang diambil. Sementara itu, perempuan yang berusia 19 tahun dianggap sudah dewasa dan mampu menjalani kehidupan rumah tangga. Jika dilihat dari perspektif teori maslahah mursalah, hal ini berkaitan dengan empat unsur utama yang dilindungi oleh agama, yang menjadi tujuan awal pensyari’atan hukum. Keempat unsur tersebut adalah pemeliharaan keturunan, jiwa, akal, dan harta dalam konteks keluarga. Isu mengenai batas minimal usia untuk menikah ini merupakan ranah ijtihadiyah yang selalu terbuka untuk perubahan seiring dengan perkembangan kondisi, masyarakat, waktu, dan tempat yang memerlukan penyesuaian..Kata Kunci: Transformasi, Usia Perkawinan, Maslahah Mursalah.